Ibadi Manuscripts at the Dār al-Kutub in Egypt (Part 2, the Inventory) | المخطوطات الإباضية في دار الكتب المصرية (الجزء الثاني, الجرد) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
Ayman Fuʾād Sayyid, Fihrist al-makhṭūṭāt nashra bi-‘l-makhṭūṭāt allatī aqtanathā al-dār min sanat 1936-1955. 3 Vol.s (Cairo, 1961-1963). This is a brief follow up to the previous post about I…
Keywords: Manuscrits – Le Caire

Ibadi Manuscripts at the Dār al-Kutub in Egypt (Part 1)| المخطوطات الإباضية في دار الكتب المصرية (الجزء الأول) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
A couple of years ago, I received a photocopy of some handwritten notes on Ibadi manuscripts in the Egyptian National Library, the Dār al-Kutub al-Miṣriyya (Figure 1). The notes are dated 1408/1988…
Keywords: Manuscrits – Le Caire

A surprising lithograph at the American University in Cairo | طبعة حجرية إباضية في مكتبة الجامعة الأمريكية في القاهرة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
Unable to travel lately, I have been searching for Ibadi lithographs listed in research libraries online. .. I did not anticipate [finding] the former owner of these volumes…
Keywords: Manuscrits – Le Caire